Discussion on estimates of the amount and rate of sea-level change across the Rhaetian–Hettangian and Pliensbachian–Toarcian boundaries (latest Triassic to Early Jurassic) - COPE, J. C. W; HALLAM, A (Journal of the Geological Society, 1998)
J. C. W. Cope writes: Hallam’s (1997) paper provides some interesting ideas about sea-level change in the Early Jurassic.His accordance of equal durations to ammonite zones and subzones may distort the picture somewhat, but I would agree that it does allow the overall calculations to be in the right order of magnitude. One of the subjects which Hallam discusses is an estimation of the time taken to deposit the Yorkshire JeRock. On the basis of the fact that it lasts one ammonite subzone, equal division of the Gradstein et al. 1994 time-scale would give it a duration of c. 630 000 years, as shown by Hallam (1997), but Hallam’s calculations from laminations suggested 3.5 Ma— a factor close to five times the other, as noted by Hallam (1997, p. 776). The most recent account of this succession of laminated bituminous shales, which total 7.53 m thick in the Whitby area, is by Howarth (1992). Hallam (1967) concluded that the laminae were probably annual, and in the same paper recorded the organic laminae as about 20 3m in average thickness and the interlaminated clays as varying from 20 to 50µm. The figure Hallam (1997) quotes for the average thickness of a bituminous shale/clay coupleted is 50µm. In a thickness of the 7 m he calculated that there would be 3 500 000 such couplets (p. 776), which led him to dismiss the idea that the couplets could be annual as their.number exceeded the time calculated by a factor of five However